The role of meta-cognitive self regulated learning strategies in enhancing language performance: A theoretical and empirical review - Rozilawati, Mahadi; Subramaniam, Ganakumaran, Assoc. Prof. Dr. (Asian Economic and Social Society, 2013)
Link to publisher's homepage at http://www.aessweb.com/